Diode Laser Treatment of Human Prostates - Razaghi, Mohammad Reza; Mokhtarpour, Hooman; Mazloomfard, Mohammad Mohsen (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Laser-assisted vaporization of prostate tissue by means of the potassiumtitanyl- phosphate (KTP) laser is in clinical use. Alternative laser sources are available but are lacking clinical experience.The 980 nm wavelength diode laser provides good hemostasis, in addition to a more rapid ablation rate. The aim of this study is approving the capability, feasibility, and good post-operative outcome of vaporization of prostate by means of a diode laser in a long-term follow up. METHODS: The light (980 nm, 100 W) of a diode laser was transmitted to prostate tissue. The study included 70 men suffering from bladder outlet obstruction due to benign prostatic hyperplasia (BPH). The prostatic lobes were vaporized within the prostatic capsule. Post-operative outcome and voiding were evaluated during a follow-up period of 24 months. RESULTS: During surgery, no significant blood loss or any fluid absorption occurred. Catheters were removed in the 20.1±4.6 hours. All patients except two were satisfied with their voiding outcome. After removing the catheter, the mean peak urine flow rate significantly increased from 6.8±2.5 ml/s pre-operatively to 15.6±3.1 ml/s postoperatively. No evidence of urgency, dysuria, hematuria, or incontinence was observed. Four patients required re-catheterization, and two of them needed consecutive TURP. After a 1- month, as well as after a 6-month, a 12-mouth, and a 1-year follow-up, all patients were still satisfied with the outcome. CONCLUSION: This long term experience showed that 100 W-980 nm-diode-laser vaporization prostatectomy was feasible and appeared to be safe and effective for quickly relieving bladder outlet obstruction due to BPH.